The Survey of the Knowledge, Attitude and AIDS Prevention Behavior Among the Registrational Married Couples, Muang district, Nakornratchasima Province - Kamonped, Srisamorn (Journal of Health Science of Thailand, 1995)
This descriptive study was done by interviewing 100 couples (200 persons) who had come to married registers at the Registry Office of Muang District, Nakornratchasima province, during March 1 to May 31,1994.The objective of this study was to assess the knowledge, attitude, media accessibility and preventional behavior on AIDS. It was found that most of the couples were in the moderate level of the knowledge and attitude towards AIDS, 74% and 68.5% respectively. The score (mean) of knowledge and attitude between males and females were not different (P>0.10). Regarding to the information accessibility, the most accessible media was television and radio and news-paper, 98.91% and 90.5% respectively. About preventional behavior on AIDS, 38% of the samples used to have their blood examined for HIV and most of them were males (51%). If their blood examination for HIV were positive, 97.5% of the samples thought that they should use contraceptive method, 42% of the samples thought that they should not have sexual intercourse, while 40% of the samples thought that they could have sexual intercoure by using condoms and 15% of the samples thought that they could have sexual intercourse without using condoms. In the area of behavioral risk of HIV infection among males, 70% of males used to have sexual intercourse before married and 74.29% of them did not or rarely use condoms. Furthermore, 88.57% of males used to have sexually transmited disease and 74.19% of them have ineffective treatment methods.